A Stimuli‐Responsive Zirconium Metal–Organic Framework Based on Supermolecular Design. Issue 36 (24th July 2017) - Krause, Simon; Bon, Volodymyr; Stoeck, Ulrich; Senkovska, Irena; Többens, Daniel M.; Wallacher, Dirk; Kaskel, Stefan
Abstract: A flexible, yet very stable metal–organic framework (DUT‐98, Zr6 O4 (OH)4 (CPCDC)4 (H2 O)4, CPCDC=9‐(4‐carboxyphenyl)‐9 H ‐carbazole‐3, 6‐dicarboxylate) was synthesized using a rational supermolecular building block approach based on molecular modelling of metal–organic chains and subsequent virtual interlinking into a 3D MOF. Structural characterization via synchrotron single‐crystal X‐ray diffraction (SCXRD) revealed the one‐dimensional pore architecture of DUT‐98, envisioned in silico. After supercritical solvent extraction, distinctive responses towards various gases stimulated reversible structural transformations, as detected using coupled synchrotron diffraction and physisorption techniques. DUT‐98 shows a surprisingly low water uptake but a high selectivity for pore opening towards specific gases and vapors (N2, CO2, n ‐butane, alcohols) at characteristic pressure resulting in multiple steps in the adsorption isotherm and hysteretic behavior upon desorption. Abstract : Switchability meets stability : A flexible, yet very stable metal–organic framework (DUT‐98, Zr6 O4 (OH)4 (CPCDC)4 (H2 O)4, CPCDC=9‐(4‐carboxyphenyl)‐9 H ‐carbazole‐3, 6‐dicarboxylate) was synthesized using a rational supermolecular building block approach based on molecular modelling. DUT‐98 shows a surprisingly low water uptake but a high selectivity for pore opening towards specific gases and vapors.